Investigation of polarization transformations performed with a refractive bi-conical axicon using the FDTD method - P.A. Khorin; A.M. Algubili; S.A. Degtyarev; S.K. Sergunin; S.V. Karpeev; S.N. Khonina (Компьютерная оптика)
We investigate polarization transformations carried out with a refractive bi-conical axicon using the FDTD method. The approach is based on the transformation of a circularly polarized optical beam into an azimuthally polarized beam due to the use of a single refractive element with two conical surfaces. On the inner surface of the element, polarization conversion occurs due to the reflection and refraction of rays at the Brewster angle, while the outer surface operates as a converted beam collimator. The distributions of the components of the electric field vector and the polarization vector at different distances from the optical element are considered as criteria for a successful polarization transformation. By numerical simulation of the performance of a bi-conical axicon made of glass with a refractive index of n = 1.4958, the efficiency of the proposed approach for a circularly polarized Gaussian beam with a wavelength of λ = 1.5 µm is shown. The proposed element is shown to be immune to chromatic aberrations in a significant range of changes in the refractive index of the element material and incident wavelengths (1.5 ≤ n ≤ 1.7; 1 μm ≤ λ ≤ 1.5 μm).